LP or not LP, that is the question: gold standard or unnecessary procedure in subarachnoid haemorrhage?. Issue 9 (11th June 2013) - Stewart, Hannah; Reuben, Adam; McDonald, James
Abstract : Objective: To measure the sensitivity of modern CT in patients presenting to the emergency department and evaluated for possible subarachnoid haemorrhage, with particular attention to those presenting within 12 h of ictus. Design: Retrospective cohort study. Setting: Large district general hospital emergency department seeing 73 500 new attendances per year. Participants: Patients presenting to the emergency department and screened for suspected subarachnoid haemorrhage. Outcome measures: Subarachnoid haemorrhage was defined by either the presence of subarachnoid blood on CT, positive CSF spectrophotometry defined by national guidelines or aneurysm identified on subsequent angiography if either of the former were equivocal. Results: 244 patients were screened for subarachnoid haemorrhage during the 24 months between March 2006 and April 2008 (mean age 48.5 years). The sensitivity of CT overall for subarachnoid haemorrhage was 93.8% (95% CI 84% to 98%) increasing to 95% (95% CI 82% to 99%) if performed within 12 h of ictus. Conclusions: While modern CT has a high sensitivity for the diagnosis of acute subarachnoid haemorrhage, particularly within 12 h of ictus, it is still not sufficient to act as the sole diagnostic tool, and patients with a negative CT will require further investigation with a lumbar puncture.